Androgynous democracy : modern American literature and the dual-sexed body politic - Shaheen, Aaron (University of Tennessee Press, 2010)
"Androgynous Democracy examines how the notions of gender equality propounded by transcendentalists and other nineteenth-century writers were further developed and complicated by the rise of literary modernism. Aaron Shaheen specifically investigates the ways in which intellectual discussions of androgyny, once detached from earlier gonadal-based models, were used by various American authors to formulate their own paradigms of democratic national cohesion. Indeed, Henry James, Frank Norris, Charlotte Perkins Gilman, John Crowe Ransom, Grace Lumpkin, W.E.B. Du Bois, and Marita Bonner all expressed a deep fascination with androgyny - an interest that bore directly on their thoughts about some of the most prominent issues America confronted as it moved into the first decades of the twentieth century." "Shaheen not only considers the work of each of these seven writers individually, but he also reveals the interconnectedness of their ideas. He shows that Henry James used the concept of androgyny to make sense of the discord between the North and the South in the years immediately following the Civil War, while Norris and Gilman used it to formulate a new model of citizenship in the wake of America's industrial ascendancy. The author next explores the uses Ransom and Lumpkin made of androgyny in assessing the threat of radicalism once the Great Depression had weakened the country's faith in both capitalism and religious fundamentalism. Finally, he looks at how androgyny was instrumental in the discussions of racial uplift and urban migration generated by Du Bois and Bonner."--Jacket